Parametric Optimization of Belt Conveyors by Energy Efficiency Criterion - O. S. Kuropiatnyk (Nauka ta progres transportu, 2021)
Purpose. The purpose of this work is to substantiate the optimal values of the belt conveyor parameters, at which the specific energy consumption for the cargo transportation takes on the lowest value. Methodology. The substantiation of the optimal values of the belt conveyor parameters was carried out by minimizing the function of specific energy consumption, which represents the energy consumption for the transportation of a cargo weighing 1 kg at a distance of 1 m. In the course of research, the drive force was determined using the contour bypass meth-od. In this case, the specific loads from the transported cargo, belt and roller supports were presented as functions of the belt width. To establish the optimal values of the conveyor productivity and belt speed, the belt width was presented as a function of these values, taking into account the physical and mechanical properties of the transported cargo, the design features of the roller supports and the belt angle. Findings. I obtained the dependences of specific energy consumption on the design parameters of the conveyor. Their analysis made it possible to identify the opti-mal values of the belt width, conveyor productivity, belt speed, and the optimal ratio of the last two values for dif-ferent types of transported cargo. It is noted that the results obtained can be supplemented by carrying out calcula-tions according to the formula given in this work. It has been established that the optimal value of the belt width depends only on the belt angle and on the coefficients that determine the energy losses, in particular the movement resistance coefficient of the belt; the influence of the specified coefficient increases with an increase in the belt angle. In addition, the optimal value of the belt width does not depend on the conveyor length, its productivity and belt speed. Originality. The dependences of the specific energy consumption on the design parameters of the belt conveyor were obtained, which made it possible to establish the optimal values of the belt width and the ratio of the conveyor productivity to the belt speed. Practical value. The results of this work can be used in the design of energy-efficient belt conveyors, which are characterized by the lowest specific energy consumption for cargo transportation.